Large Hip Impingement Area and Subspine Hip Impingement in Patients With Absolute Femoral Retroversion or Decreased Combined Version. Issue 2 (21st February 2023) - Boschung, Adam; Antioco, Tiziano; Novais, Eduardo N.; Kim, Young-jo; Kiapour, Ata; Tannast, Moritz; Steppacher, Simon D.; Lerch, Till D.
Background: It remains unclear if femoral retroversion is a contraindication for hip arthroscopy in patients with femoroacetabular impingement (FAI). Purpose: To compare the area and location of hip impingement at maximal flexion and during the FADIR test (flexion, adduction, internal rotation) in FAI hips with femoral retroversion, hips with decreased combined version, and asymptomatic controls. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Twenty-four symptomatic patients (37 hips) with anterior FAI were evaluated. All patients had femoral version (FV) <5° according to the Murphy method. Two subgroups were analyzed: 13 hips with absolute femoral retroversion (FV <0°) and 29 hips with decreased combined version (McKibbin index <20°). All patients were symptomatic and had anterior groin pain and a positive anterior impingement test ; all had undergone pelvic computed tomography (CT) scans to measure FV. The asymptomatic control group consisted of 26 hips. Dynamic impingement simulation of maximal flexion and FADIR test at 90° of flexion was performed with patient-specific CT-based 3-dimensional models. Extra- or intra-articular hip impingement area and location were compared between the subgroups and with control hips using nonparametric tests. Results: Impingement area was significantly larger for hips with decreased combined version (<20°) versus combined version (≥20°) (mean ± SD; 171 ± 140 vs 78 ± 55 mm 2 ; P = .012) and was significantly larger for hips with FV <0° (absolute femoral retroversion) vs FV >0° ( P = .025). Hips with absolute femoral retroversion had a significantly higher frequency of extra-articular subspine impingement versus controls (92% vs 0%; P < .001), compared to 84% of patients with decreased combined version. Intra-articular femoral impingement location was most often (95%) anterosuperior and anterior (2-3 o'clock). Anteroinferior femoral impingement location was significantly different at maximal flexion (anteroinferior [4-5 o'clock]) versus the FADIR test (anterosuperior and anterior [2-3 o'clock]) ( P < .001). Conclusion: Patients with absolute femoral retroversion (FV <0°) had a larger hip impingement area, and most exhibited extra-articular subspine impingement. Preoperative FV assessment with advanced imaging (CT/magnetic resonance imaging) could help to identify these patients (without 3-dimensional modeling). Femoral impingement was located anteroinferiorly at maximal flexion and anterosuperiorly and anteriorly during the FADIR test.